On freedom underlain by trauma in the works of Leopold Buczkowski - Winiecka, Elżbieta (Porównania, 2024)
This article is about Leopold Buczkowski's experimental writing. Drawing on his prose, as well as the writer's wartime diary and his photographic and visual art work, the author shows that his formal explorations in the sphere of the novel can be explained to a much greater extent than previously thought by the writer's personal experiences. Traumatic experiences from his youth (the genocide in his native Podolia and the loss of his home, the death of his two brothers, his participation in the Warsaw Uprising) left their mark on his personality and made all his later interdisciplinary work a form of self-therapy, as well as a space of freedom and independence. Writing, composing, drawing and painting were treated by Buczkowski as a sphere of searching for his own individual truth, which he tried to express in artistic matter. Freedom and trauma are treated as key words for understanding the work of the author of Bathing in Lucca.